Aragonite saturation states in estuaries along a climate gradient in the northwestern Gulf of Mexico - Hu, Xinping; Yao, Hongming; McCutcheon, Melissa R.; Dias, Larissa; Staryk, Cory J.; Wetz, Michael S.; Montagna, Paul A. (Frontiers in Environmental Science, 2022)
In the northwestern Gulf of Mexico (nwGOM), coastal climate shifts abruptly from the humid northeast to the semiarid southwest within a narrow latitudinal range. The climate effect plays an important role in controlling freshwater discharge into the shallow estuaries in this region. In addition to diminishing freshwater runoff down the coast, evaporation increases substantially. Hence these estuaries show increasing salinity along the coastline due to the large difference in freshwater inflow balance (river runoff and precipitation minus evaporation and diversion). However, this spatial gradient can be disrupted by intense storm events as copious amount of precipitation leads to river flooding, which can cause temporary freshening of these systems in extreme cases, in addition to freshwater induced ephemeral stratification. We examined estuarine water aragonite saturation state (Ωarag) data collected between 2014 - 2018, covering a period of contrasting hydrological conditions, from the initial drought to multiple flooding events, including a brief period that was influenced by a category 4 hurricane. Based on freshwater availability, these estuaries exhibited a diminishing Ωarag fluctuation from the most freshwater enriched Guadalupe Estuary to the most freshwater-starved Nueces Estuary. While Ωarag values were usually much higher than the threshold level (Ωarag = 1), brief freshwater discharge events and subsequent low oxygen levels in the lower water column led to episodic corrosive conditions. Based on previously obtained Ωarag temporal trends and Ωarag values obtained in this study, we estimated Time of Emergence (ToE) for Ωarag. Not only did estuaries show decreasing ToE with diminishing freshwater availability, the subembayments of individual estuaries that had less freshwater influence also had shorter ToE. This spatial pattern suggests that planning coastal restoration efforts, especially for shellfish organisms, should focus on areas with longer ToE.